2022
DOI: 10.3390/agronomy12020494
|View full text |Cite
|
Sign up to set email alerts
|

Ebb-and-Flow Subirrigation Improves Seedling Growth and Root Morphology of Tomato by Influencing Root-Softening Enzymes and Transcript Profiling of Related Genes

Abstract: Ebb-and-flow subirrigation is a promising strategy to increase water use efficiency, avoid waterlogging or drought conditions, and promote the overall growth of vegetable crops. The aim of this study was to evaluate the seedling growth, root morphology, activities of root-softening enzymes, and transcript profiling of those enzyme-related genes in tomato under top sprinkle irrigation and ebb-and-flow subirrigation. The results showed that ebb-and-flow subirrigation could significantly improve stem diameter, ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 81 publications
0
2
0
Order By: Relevance
“…Tomatoes are produced in Pakistan over an area of 58,359 hectares, with an average yearly yield of 550,979 tonnes 3 , 4 . Tomatoes may be grown in a wide range of climates, although they face a variety of abiotic stresses, including high temperatures 5 – 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Tomatoes are produced in Pakistan over an area of 58,359 hectares, with an average yearly yield of 550,979 tonnes 3 , 4 . Tomatoes may be grown in a wide range of climates, although they face a variety of abiotic stresses, including high temperatures 5 – 7 .…”
Section: Introductionmentioning
confidence: 99%
“…The contrasting responses to the sub-irrigation could be due to each plant species' tolerance to high EC and the specific demand for nutrients [4,31]. In our study, the decrease in fruit According to Wang et al [36] the ebb and flow sub-irrigation technique is a promising strategy to promote the growth of vegetable crops. Our results concur with that statement, as they showed that tomatoes may be grown under sub-irrigation with no detrimental effects on fruit yield as long as the EC of the nutrient solution does not exceed 2.0 dS m −1 .…”
Section: Fruit Yieldmentioning
confidence: 62%
“…Horticulturae 2023, 9, x FOR PEER REVIEW 6 of 15 et al [26] indicated that if the concentration of nutrients or the EC in the nutrient solution exceeds the optimal range, it reduces the growth and yield of plants in closed hydroponic systems as they are under more severe osmotic conditions. According to Wang et al [36] the ebb and flow sub-irrigation technique is a promising strategy to promote the growth of vegetable crops. Our results concur with that statement, as they showed that tomatoes may be grown under sub-irrigation with no detrimental effects on fruit yield as long as the EC of the nutrient solution does not exceed 2.0 dS m −1 .…”
Section: Fruit Yieldmentioning
confidence: 99%
“…The use of photovoltaic systems to power irrigation systems operating in areas remote from electricity grids is not a new topic. It has been addressed many times in the pages of various journals [KHAN 2012;MUHAMMAD et al 2014;WANG et al 2022]. However, the authors of these works did not pay special attention to the quality of the energy used to power the pumps.…”
Section: Resultsmentioning
confidence: 99%